Mild Cognitive Impairment Associated with Pesticides use Among Vegetable Farmers and Their Wives in Sukorambi Village Jember Regency - Fidiyaningrum, Rosidah; Sujoso, Anita Dewi Prahastuti; Indrayani, Reny (The Indonesian Journal of Occupational Safety and Health, 2024)
Introduction: Mild Cognitive Impairment (MCI), according to several studies, has been discovered to be related to exposure to pesticides. Sukorambi Village is the largest vegetable producer village in Jember Regency and pesticides are used in the vegetable cultivation process. This study aimed to analyze the relationship between the age of vegetable farmers and the frequency of pesticide spraying with the incidence of MCI and to analyze differences in the incidence of MCI in farmers and their wives. Methods: This research is an analytical research with a cross-sectional design which was carried out in Sukorambi Village, from June to December 2022. The samples of this research are 142 people, obtained from a proportional stratified random sampling technique and represented groups of farmers in each hamlet. In this case, the research variables include age, frequency of pesticide spraying, as well as the incidence of MCI in vegetable farmers and their wives. Data were further collected through direct interviews, which were then analyzed through bivariate analysis using Spearman and paired t tests. Results: The results showed that the majority of vegetable farmers were above 55 years old and most of them sprayed pesticides for 3-4 and 5-6 times a month. Most farmers and their wives experience MCI. Conclusion: The farmer's age and the frequency of spraying pesticides are related to the incidence of MCI in farmers. There is a significant difference between the incidence of MCI in vegetable farmers and their wives, where MCI is more experienced by vegetable farmer wives.